Treats to the integrity of the Croatian Medical Journal - Marušić, Matko (Array, 2007)
The Croatian Medical Journal (CMJ) was founded in 1992.It aims to present medical research from small scientific communities and developing countries (1), and serve as an educational site of excellence to foster research and discussion in academia (2).Internationally, the journal became indexed in Medline in 1998 and in the Thomson Scientific (formerly Institute for Scientific Information) databases in 1999 (3).Its impact factor (0.823 for 2006) puts it in the middle of the Thomson Scientific Journal Citation Reports category “Medicine, General and Internal” but our primary goal is to publish the research from the so-called “scientific periphery” and to make this research available to the world by providing free access to all our content (4). The CMJ is a member of the International Committee of Medical Journal Editors (ICMJE), and Croatia is the place where the first ICMJE statement on the registration of clinical trials was formulated (5)